The Representation of Literacy as Salvation in Peter Weir's Dead Poets Society - Ajeng Eka Noviyanty (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Literacy is usually understood as the cognitive ability to read and write. The theme of literacy is rarely used in literary works. Literacy can be represented in various forms, one of which is literacy as a salvation. The study aims to reveal how literacy serves as healing and leads to salvation. New Literacy Studies (NLS) perspective of literacy as social practice is used as a conceptual framework. The purpose of this study is to present a representation of literacy as a salvation on the character of Neil in the film Dead Poets Society. The focus of this study is on the main character named Neil Perry who is a student who lives in a family that demands him to be what his parents want him to be. Then there was one teacher named John Keating who taught them about poetry and its application in life. A poetry community that has an impact on the lives of students where literacy as a salvation is the main topic that will be studied. This study uses the New Literacy Studies Theory (Street, 2003) to be realized in the film. The results of the study show that literacy can be a salvation for Neil Perry.